Aktivitas Antibakteri Fraksi Daun Aka Lambuang - Alen, Yohannes; Rustini, .; Honesty, Resta (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
Antibacterial activity tests were conducted on the leaf fraction of Aka lambuang (Merremia peltata (L.)Merr.) by dilution method and microplate reader towards Staphylococcus aureus and Escherichia coli. The results showed that activity performed at the minimum inhibitory concentration of 500 ppm and 1000 ppm respectivelyKeywords :  Merremia peltata, antibacterial, microplate reader.